Risk stratification in patients with upper gastrointestinal submucosal tumors undergoing submucosal tunnel endoscopic resection - Lv, Yong; Li, Shaohua; Lv, Xiuhe; Liu, Qing; Zheng, Yu; Su, Yang; Yang, Changbin; Pan, Yanglin; Yao, Liping; Xie, Huahong (Frontiers in Medicine, 2022)
Background: A substantial heterogeneity exists in the patients with upper gastrointestinal submucosal tumors (SMTs). This study aimed to identify predictors of long procedure time (≥ 60minutes), occurrence of procedure-related complications and long hospital stay (≥ 6 days) in patients with SMTs undergoing submucosal tunnel endoscopic resection (STER) and stratify risk base on the predictors. Methods: Sixty-six consecutive patients with upper gastrointestinal SMTs undergoing STER between Jan 2013 and Dec 2016 were retrospectively included. Binary logistic regression models were developed to identify predictors of outcomes. Receiver operating characteristic (ROC) curves were constructed to evaluate the discrimination of tumor size. Results: Complete resection and en bloc resection of tumor were achieved in 66 (100%) and 64 patients (97%), respectively. Twenty-seven patients (41%) had a long procedure time, 10 (15%) developed STER-related complications and 17 (26%) had a long hospital stay. On multivariable analysis, tumor size was independent predictor of long procedure time (OR1.37, 95%CI 1.13 - 1.67; p=0.001), occurrence of complications (OR 1.06, 95%CI 1.01 - 1.10; p=0.012) and long hospital stay (OR 1.05, 95%CI 1.01 - 1.09; p=0.035). ROC curves identified 25 mm of tumor size as the best cutoff; those who had a tumor above this value had a 76-fold risk of long procedure time, 8.56 folds risk of occurrence of complications and 6.35 folds risk of long hospital stay. Conclusions: Patients with tumor size ≥ 25 mm had longer procedure time, higher risk of STER-related complications and longer hospital stay, therefore they should be classified as high-risk group.